Effects of cocoa clones and fermentation times on physical and chemical characteristics of cocoa beans (Theobroma cacao L.). (May 2019) - Assa, A; Rosniati,; Yunus, M R
Abstract: The effects of cocoa clones and fermentation time on the physical and chemical characteristics of cocoa beans has been examined. This study used cocoa pods of superior clones, namely Sulawesi 1, Sulawesi 2, and MCC 02 clones cultivated in East Luwu, South Sulawesi, Indonesia. Prior to the fermentation, the mature cocoa pods were stored for six days. Fermentation took place for 24, 48, 72, 96, and 120 hours using fermentation boxes made of styrofoam with the capacity of box is 7 kg of wet beans. The drying of the cocoa beans used sun drying method. The results showed that the interaction between fermentation time and type of clones have significantly affected moisture content, proportion of cocoa nibs and shells, and fat content; but the interaction of the both had no significant effect on pH of cocoa nibs and FFA content. In general, the Sulawesi 2 clone had better physical and chemical characteristics than those of the Sulawesi 1 and MCC 02 clones.